FLESHING OUT THE PROVISIONS FOR PROTECTING FOREIGN INVESTMENT - Hossain, Mohammad Belayet (Faculty of Law, Universitas Sebelas Maret, 2018)
This article aims to analyse the jurisprudence developed by international courts and tribunals with regard to the standard of treatment of foreign investors, with particular focus on issues concerning expropriation. In doing so, it will analyse some of the standard-setting decisions and far-reaching implications of: the Iran-US Claims Tribunals, the International Court of Justice and the ICSID. It will also examine the recent trend in jurisprudence on the so-called regulatory takings of foreign investment. It will explore: (a) how the decisions of international courts and tribunals have ‘fleshed out’ the principles of the law of foreign investment on, inter alia, the definition of expropriation and nationalisation and determination of the quantum of compensation; (b) how the frontiers of expropriation have been extended to cover regulatory takings